Analysis of Rooftop Solar Power Plant Development Potential in Magelang City: A Case Study of Office Buildings, Universities, And Hotels (Journal of Renewable Energy and Mechanics, 2025)
The utilization of solar energy as a renewable energy source has become a priority in supporting sustainable energy transitions in Indonesia. This study analyzes the potential for installing rooftop solar power plants (PLTS) in office buildings, universities, and hotels in Magelang City. The research method involves measuring roof areas using Google Maps imagery and simulating energy production through the Global Solar Atlas. The analysis indicates that with a 20% utilization rate of potential roof areas, the corresponding installed capacity can reach 230.720–333.560 kWp. Energy production estimates show outputs of up to 11,000 kWh/month for an 80 kWp capacity. These findings underscore Magelang City's potential to support renewable energy transitions through multi-faceted collaboration. This study provides a foundation for developing sustainable energy policies in urban areas.